Paradigm shift in family law - Sánchez Casal, Suevia (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2020)
Social changes in western world have determined major transformations in the conformation and the relationships between family members, and have impacted particularly on family law, which was conceived under the traditional vision, typical of the 19th century. This article addresses the historical evolution of family up to the present day, as well as the social changes and scientific advancements that determined the gradual deterioration of family law foundations, mainly in two of its fundamental institutions: marriage and filiation. Finally, the current situation in Uruguay is approached, underscoring the need to rebuild family law on new bases, in accordance with today’s social requirements, to guarantee its permanence in time.